The effect of football sponsorship in fans purchase intention: an application to beer products - Caetano, Gonçalo Miguel Ribeiro de Sá Pereira (2020)
Football have been present in the Portuguese culture for a long time, it is a sport of emotions that influence thousands of individuals. Football clubs sponsorship in the last years have gained a huge importance for the amount of money brands have been investing. Companies look at football clubs as very important part of their marketing strategy since it is a channel that guarantees huge levels of exposition. This research has the objective of studying how by fact that a brand sponsors an individual football club or its rivals it will influence its purchase intention, additionally it was tested how this effect is amplified with the increase on levels of fandom. This academic study analysis the Portuguese Football sponsorship culture with focus on the beer brands Sagres and Super Bock and the three main football clubs in Portugal. Sagres sponsors Benfica and Super Bock sponsors Sporting and FC Porto. These beer brands as well as the clubs are rivals, this rivalry is used in the study. The study shows that the purchase intention of a football supporter is affected by the brands that sponsor his/her club and also the ones sponsoring the rivals teams. Additionally, this research shows that this effect increases as the level of fandom of the individuals increases. This investigation provides some support for companies that want to understand the extent of the effects of sponsoring a big football team in Portugal by providing clues on how the purchase intention is affected.